Development of Socioscientific Case-Based Worksheet in Biology Topics for IX Grade Junior High School to Improve Communication-Collaboration Performance - Muhyiatul Fadilah; Syifa Ananda; Nada Aulia Asri; Rahmadhani Fitri; Heffi Alberida; Aldeva Ilhami* (Jurnal Pendidikan Sains Indonesia, 2022)
Case-based learning is a recommendation for the achievement of 21st-century skills. Empirical facts show any limitations of science teaching materials that model the integration of cases into science learning topics in secondary schools. Socioscientifc issues are potential cases for Biology learning. Unfortunately, learning tools for this such issues are relatively rare. This study aims to develop a case-based student worksheet with socioscientific issues. We conducted development research applying the 4D model, which is limited to 3 stages: define, design, and develop. The research instrument consisted of validation sheets, practicality questionnaires, and observation sheets for measuring communication and collaboration performance. The research population students who learn science in junior high school. The sample is determined purposively. We choose 52 science students from one of the junior high schools in Padang City and 17 prospective science teacher students who registered as participant of Learning Material Development Course. Data processing used descriptive statistics (percentage) to inform validity criteria gained, while inferential statistics (Mann-Whitney test) were applied to compare the differences of communication and collaboration scores among science students and science teacher candidates during the practicality stage. The results showed that the socioscientific case-based worksheets reached the criteria of 1) being very valid, 2) practical and very practical for users (teachers, students, and prospective science teacher students), and 3) having a significant effect on the collaboration-communication performance of science students and science teacher candidate. Otherwise, communication collaboration performance indicators that need to be considered for improving 21st-century skills are responding to large group audiences, presenting ideas, conducting inter-group discussions, and drawing conclusions